Identification of Non-Formal Education Programs and Analysis of Accreditation in Indonesia - Suwandi; Tantra, Dewa Komang (American Journal of Education and Learning, 2019)
The purpose of this study is to investigate the condition of non-formal educational programs (NEP) and units in each region in Indonesia. A survey method comprising questionnaires, interviews and documentation was conducted in January 2016 to identify programs and units throughout the country. The sample was determined by purposive sampling inside and outside Java Island regions. Data were analyzed by reviewing previous accreditation analysis in 2015 reported by the National Accreditation Board for Non-Formal Education (NAB-NEP). The results shows that there were 7,757 NEP programs and units identified as accredited by NAB-NEP. The national distribution of NEP admittances ready for accreditation was dominated by Java region (2,301 or 48.4%) in 2016. Although this was proportional to the number of NEPs in the six provinces of Java, it appears that NEPs from other provinces were less active or unable to meet the requirements. The other provinces can be summarized as follows: Sumatra (1,252 or 26.3%), Kalimantan (544 or 11.4%), Sulawesi (275 or 5.8%), NTB and NTT (121 or 2.5%), Papua and West Papua (30 or 0.6%), and Maluku and North Maluku (3 or 0.1%).